Progress in utilisation of waste cooking oil for sustainable biodiesel and biojet fuel production. (1st November 2020) - Goh, Brandon Han Hoe; Chong, Cheng Tung; Ge, Yuqi; Ong, Hwai Chyuan; Ng, Jo-Han; Tian, Bo; Ashokkumar, Veeramuthu; Lim, Steven; Seljak, Tine; Józsa, Viktor
Graphical abstract: Highlights: Waste cooking oil (WCO) recycling models and practices are reviewed. The processing pathways of converting WCO into biofuels are examined. Energy balance for biodiesel conversion using different techniques is analysed. Conversion of WCO into biojet fuel is feasible using hydrogenation method. Biofuel production using WCO is sustainable and reduces GHG emissions. Abstract: The increase in human consumption of plant and animal oils has led to the rise in waste cooking oil (WCO) production. Instead of disposing the used cooking oil as waste, recent technological advance has enabled the use of WCO as a sustainable feedstock for biofuels production, thereby maximising the value of biowastes via energy recovery while concomitantly solving the disposal issue. The current regulatory frameworks for WCO collection and recycling practices imposed by major WCO producing countries are reviewed, followed by the overview of the progress in biodiesel conversion techniques, along with novel methods to improve the feasibility for upscaling. The factors which influence the efficiency of the reactions such as properties of feedstock, heterogenous catalytic processes, cost effectiveness and selectivity of reaction product are discussed. Ultrasonic-assisted transesterification is found to be the least energy intensive method for producing biodiesel. The production of bio-jet fuels from WCO, while scarce, provide diversity in waste utilisation if problems such as carbon chain length, requirements of bio-jet fuel properties, extreme reaction conditions and effectiveness of selected catalyst-support system can be solved. Technoeconomic studies revealed that WCO biofuels is financially viable with benefit of mitigating carbon emissions, provided that the price gap between the produced fuel and commercial fuels, sufficient supply of WCO and variation in the oil properties are addressed. This review shows that WCO is a biowaste with high potential for advanced transportation fuel production for ground and aviation industries. The advancement in fuel production technology and relevant policies would accelerate the application of sustainable WCO biofuels.